FORMULASI SEDIAAN GEL EKSTRAK ETANOL DAUN BIDARA (Ziziphus mauritiana L) SEBAGAI PENYEMBUHAN LUKA BAKAR TERHADAP TIKUS PUTIH JANTAN - Simorangkir, Delisma Marsauli (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2025)
Burn wound treatment is still carried out simply and is generalized with a certain pattern for various wound conditions and problems. One of the natural ingredients (herbs) that has an effect as a medicine for burns is the Bidara plant (Zizipus mauritiana L.), which has antibacterial, anti-viral, antiseptic properties and its function in regenerating and repairing skin cells. This research is a type of experimental research. Sampling was carried out purposively. The research procedure consisted of several stages, namely making reagents, phytochemical screening tests, and examining the characteristics of the ethanol extract. The research procedure consisted of several stages, namely making reagents, phytochemical screening tests, and examining the characteristics of the ethanol extract. The results of microscopic examination of sapodilla leaf simplicia powder showed the presence of stomata, tissue cells, parenchymal tissue and normal hair. In the One Way Anova results table for total burn wound healing after treatment, it shows a sig value <0.05 with the burn wound healing value from day 1 showing a significant value: 0.000. This shows that there is a significant difference in the value of burn wound healing from day 1. 1st to 14th day. The identification results of Bidara leaf extract (Zizipus mauritiana L.) showed that it positively contained secondary metabolite compounds, namely alkaloid compounds, flavonoid compounds, tannin compounds, saponin compounds and terpenoid compounds. The ethanol extract gel preparation of bidara leaves is less effective than bioplacenton for healing burns.